TARJIMADA TABU: LINGVOMADANIY TO‘SIQLAR (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article deals with the current linguistic and cultural problem in Translation: taboo. Its cultural, sociological, and linguistic aspects are highlighted as challenges for translators. The thesis identifies common translation strategies such as euphemism, omission, substitution, and cultural adaptation as solutions to the problem.